Mapping land cover changes in Cherating, Pahang using gis - Muhammad Suharni, Muhammad Luqman; Taib, Siti Noor Aifa; Shammodin, Muhammad Shaheed; Ahmad, Zuhairi (Universiti Teknologi Malaysia, 2017)
This study is to determine the land cover changes within 20 years. Chalets, resorts, human settlements, roads, shrimp farm, jetty and tourist information centre were developed over the years. Methodology: Remote sensing and Geographical Information System (GIS) have been performed on Cherating area to determine the expansion of urban and degradation of mangrove area by processing five Landsat satellite images from 1997, 2002, 2006, 2013 and 2016 using supervised classification. Findings: Based on supervised classification of urban group, the expansion of development or urban area can be observed in 1997 (58.45 ha) and in 2016 (108.70 ha), showing an increase by 85.96% in 20 years. Contribution: A significant increase in coastal development urges long term monitoring in Cherating mangrove area to ensure the survival of biodiversity and encourage development in a sustain manner.